Automação residencial - Lemos, Alan de Matos [UNESP] (2017)
This graduation work will present an implementation of a home automation system in a scheme representing a residence. This system uses a central automation Arduino Uno board, which is capable of controlling several processes within a residence as the user wants. A system that interacts with the user's Android. We will also explore issues of good practices, equipment and procedures necessary for its implementation. For this project were developed circuits Module Relay Driver 4 Channels 5V DC, module with Arduino Ethernet Shield R3, components Modulo Relay Driver 4 Channel DC 5V, Servo Motor (Cys model S0009 analog servo), A 12V cooler, LDR sensor horn, LM35 temperature sensor and an I2C module, this device is responsible for saving outputs from the LCD.